Indigenous Cellulosic Raw Materials for the Production of Pulp, Paper and Board Part XII. Chemlcal Pulps and Writing and Printing Papers from Ulla Grass (Themeda arundinacea, Ridley) - Bhat, R. V.; Roy, D. P. (Indian Forester, 1953)
Laboratory experiments on the chemical pulping of ulla grass (Themeda arandinacea, Ridley; syn. Anthistiria gigantia, Cav.) by the soda and sulphate processes are described. Experiments were carried out on crushed as well as uncrushed grass. Results of pilot plant experiments on the production of chemical pulps and writing and printing papers are also included. A sample each of writing and printing papers made from 100% ulla grass pulp is appended. This investigation has shown that writing and printing papers of good quality can be prepared from ulla grass.